The analysis of factors contributed to delay and method to analyze the delay in construction project - Mohammad Solhi, Mohammed (2010)
Delay is one of the major problems in construction industry. Therefore, it is common for construction project to encounter delays. There are various factors identified in the project life cycle that will influence the construction time, thus leading to delay. Analyzing the various causes that contribute to project's delay is an important task to resolve it. Thus, the aim of this study is to identify the contribution factors of delay and highlight a common method for analyzing delay in construction project. Data is gathered from respondents of questionnaire survey who were involved in construction project. Microsoft Excel software was used to analyze the data collected in terms of agreed percentages of respondents and relative index value. From the survey, financial problems were identified as the main factors that lead to the delay in construction projects. As a conclusion, analysis shows that completion of the project on schedule is a difficult task to accomplish due to the complexity, multiparty and dynamic environment of construction. So, various methods have been developed in order to measure the impact of delay. It is established in this study that As-Planned CPM Technique, "But For" Analysis Using As-Planned CPM and Impacted As-Built CPM is the most preferred method of analyzing delay for construction projects.